A High-Gain and Broadband 1×8 Hexagonal Antenna Array for 28 GHz 5G Applications - Mounir, Ghizlane; El Abbadi, Jamal (Engineering, Technology & Applied Science Research, 2026)
Millimeter-wave (mmWave) fifth-generation (5G) communication systems operating at 28 GHz experience significant propagation losses, which necessitate the use of compact, high-gain, and wideband antenna arrays. In this paper, a novel 1×8 hexagonal microstrip antenna array is proposed for 5G mmWave applications. The array is designed on a Rogers RT5880 substrate with a relative permittivity of 2.2, a loss tangent of 0.0009, and a thickness of 0.45 mm. By employing a hexagonal radiating geometry and a T-junction corporate feeding network, the proposed array achieves improved current distribution and efficient aperture utilization. Simulation results demonstrate that the proposed antenna array attains a high realized gain of approximately 14.32 dB, surpassing that of several previously reported microstrip-based arrays, along with a wide impedance bandwidth of 1.84 GHz. Good impedance matching and stable radiation characteristics are maintained across the operating band. Compared with conventional patch-based arrays reported in the literature, the proposed design offers enhanced gain and bandwidth performance while preserving a compact structure. These features make the proposed hexagonal antenna array a promising candidate for 5G mmWave systems requiring high directivity, broadband operation, and compact implementation.